MOTIVATION OF EDUCATIONAL ACTIVITY OF ADULT LEARNERS AS ONE OF THE URGENT PROBLEMS OF ADDITIONAL PROFESSIONAL EDUCATION - Angela Kobleva (Вестник Северо-Кавказского федерального университета)
In the present article we discuss the relevance of the role of motivation of educational activity of adult learners as an important indicator of the efficiency of the additional professional education system. We believe that increase the productivity of learning is possible through the formation of interest and motivation of students to educational activity. We assumed that the professional development of the student, his successful adaptation of the profession and the development of professional competence is largely determined by motivation of the student to the educational and labor activities.